2003
DOI: 10.1007/s00592-003-0061-7
|View full text |Cite
|
Sign up to set email alerts
|

Body composition assessment in spinal cord injury subjects

Abstract: Total and segmental body composition (fat mass, FM; fat-free mass, FFM; bone mineral density, BMD) were evaluated in 13 sedentary spinal cord injury (SCI) subjects and in 13 able-bodied healthy males (control, C) using dual X-ray absorptiometry (DXA) and skinfold methods. In the SCI group, total FM was significantly higher (31.1+/-8.2 vs. 20.8+/-6.9%) and total FFM was significantly lower (62.2+/-8.9 vs. 73.5+/-6.4%) than in C subjects. Total BMD did not differ between the SCI and C groups (1.20+/-0.11 vs. 1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
1
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 7 publications
8
78
1
9
Order By: Relevance
“…6,22,23 Thus, despite greater fat mass in subjects with versus without SCI, body weight and BMI often do not differ. 5,6,8,9,11,22 Buchholz et al 22 found the 30 kg/m 2 BMI cutoff correctly identified only 20% of truly obese paraplegic subjects, as compared with published sensitivity values of 48-66% in able-bodied populations. [24][25][26] In the study of Buchholz et al, weight was measured using a wheelchair scale, length was measured using a length board, fat mass was determined by isotope dilution and obesity was defined by the method of Lohman.…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 95%
See 2 more Smart Citations
“…6,22,23 Thus, despite greater fat mass in subjects with versus without SCI, body weight and BMI often do not differ. 5,6,8,9,11,22 Buchholz et al 22 found the 30 kg/m 2 BMI cutoff correctly identified only 20% of truly obese paraplegic subjects, as compared with published sensitivity values of 48-66% in able-bodied populations. [24][25][26] In the study of Buchholz et al, weight was measured using a wheelchair scale, length was measured using a length board, fat mass was determined by isotope dilution and obesity was defined by the method of Lohman.…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 95%
“…2 Mean percent fat mass (measured by dual energy X-ray absorptiometry (DXA), isotope dilution or the threecompartment model) reported in cross-sectional studies of persons (mostly men) with chronic spinal cord injury (SCI) ranges from 23 to 35%. [4][5][6][7][8][9][10][11] The percentage of body weight as fat mass is 8-18% higher in SCI versus age-, height-and/or weight-matched able-bodied control subjects. These values are often consistent with the above definitions of obesity, and are summarized in Table 1.…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these specific markers, several studies have shown that SCI individuals have a lower total body and regional lean mass (LM), especially in lower limb, and a higher FM than controls. [7][8][9] Adipose tissue is an important secretory organ that produces various bioactive substances known as adipokines, which include leptin, tumor necrosis factor-a, adiponectin and plasminogen activator inhibitor-1 (PAI-1); they contribute to obesity-linked metabolic and vascular diseases, as well as MetS. 10 In the SCI population, correlation between adipokine levels and body composition is assumed to be different from that in general population because of differences in location of adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…However, formulas for calculating the body fat percentage did not have a good correlation to this assessment, although they are usually widely adopted in studies involving men with spinal cord injury (13,14,(19)(20)(21)(22). This limitation leads such measures to serve only for comparative analysis of the individual her/himself over time, instead of a relation to reference values.…”
Section: Introductionmentioning
confidence: 99%